Dukungan Informasional dan Emosional Keluarga dalam Perilaku Pemanfaatan Layanan Kesehatan Reproduksi Remaja - Annisa Febriana; Sigit Mulyono (Yayasan Literasi Sains Indonesia, 2022)
The adolescent age group as a population at risk of experiencing reproductive health problems requires support and attention from the family. Information support and emotional support for adolescents are the main focus of families in overcoming adolescent reproductive health problems. This study aims to determine the relationship of family informational and emotional support to the behavior of using reproductive health services by adolescents. This study uses a descriptive correlational research design with a cross sectional approach with a sample size of 370 with random sampling method. The results showed that there was a significant relationship between informational and emotional support from the family and the behavior of using reproductive health services (p-value 0.000). Behavior improvement in the use of health services needs to be improved with the support of knowledge and attention from parents of adolescents, as well as the active role of health workers in efforts to introduce adolescent reproductive health services.